Analisis Tingkat Kesiapan Pengguna Aplikasi AllMac Service Center Menggunakan Metode Technology Readiness Index (TRI) 2.0 - Ardhi Zakhirul Qolby (Fakultas Ilmu Komputer, 2025)
AllMac Service Center is an application developed to facilitate AllMac Sarana Grafika customers in maintaining and servicing digital printing machines. The AllMac Service Center application which is still running for 4 months makes users experience several problems related to user readiness, including difficulties in operating the application and difficulties in accessing the information they need. The purpose of this study is to analyze the level of readiness of AllMac Service Center application users using the Technology Readiness Index 2.0 method, analyze the segmentation of AllMac Service Center application users using TR-Based Segmentation, and provide recommendations based on user categories. In this study, a research instrument was prepared in the form of a questionnaire, which was then tested to ensure that the instrument was suitable to be used as a research instrument including validity and reliability tests. The questionnaire was distributed to respondents with the criteria of customers who had ordered service through the AllMac Service Center application at least once. This research requires 124 respondents. Furthermore, the data obtained will be processed and analyzed using the TRI 2.0 method and user segmentation will be carried out. The results showed that the level of readiness of AllMac Service Center application users fell into the medium technology readiness category with a score of 3,02. The AllMac Service Center application user segmentation analysis resulted in 3 cluster groups, namely cluster 1 which has characteristics close to the explorers cluster group with 55 members, cluster 2, the pioneers cluster group with 46 members, and cluster 3, the skeptics cluster group with 23 members.
Entry oleh Arif 2026 Maret 27
Keywords: Technology Readiness Index; TR-Based Segmentation